An evaluation of patient comfort levels during expression with a modified pumping program: a prospective proof of concept study - Manshanden, T. M. Nicole; Prime, Danielle K.; Scheele, Fedde; Velzel, Joost (Frontiers in Global Women's Health, 2024)
Introduction: This study aimed to assess if the implementation of a gentle transition of vacuum mode into a breast pump suction pattern commonly used to initiate milk production would improve user comfort while expressing during the first four days postpartum.This prospective, observational cohort study was conducted at OLVG hospital in the Netherlands in two sequential phases. Breastfeeding patients delivering >36 weeks gestation with an infant aged ≤96 hours old and a clinical indication to express milk with a breast pump were recruited. Intervention group 1 (n=40) used a hospital-grade electric breast pump with a standard breast pump suction pattern. Intervention group 2 used a hospital-grade electric breast pump with a modified breast pump suction pattern (n=40). The primary outcome was an objective assessment of comfort as measured by participants' need to reduce vacuum level during the 20 minute test session. Secondary outcomes included the total expression volume (ml) in 20 minutes pumping.The study found that the primary outcome of comfort was significantly improved with the modified breast pump suction pattern compared to the standard pattern (OR 1.29, 95% CI 1.08 to 1.6) with 86% versus 67% of participants not needing to reduce applied vacuum levels.The amount of milk expressed did not differ significantly between phases (group 1: 7.6ml (2.7-25.5ml), group 2: 12.0ml (1.2-31.5ml), p=0.43).: This study is the first to demonstrate an improvement in user comfort driven by the implementation of gentle transitions in vacuum modes in a commonly used breast pump suction pattern. Research into this novel population combining both pumping and breastfeeding in the first days after birth offers new unique insights on the requirements of breast pump suction patterns. Trial registration: Registered on clinical trials.gov NCT04619212. Date of registration